An Analysis Of Writing Teaching Strategies by English Teacher In Junior High School - Enzelina Sinaga; Novia Damayanti Br Hutabarat; Tiur Maulina Panjaitan; Erikson Saragih (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to analyze how writing teaching strategies by teacher in junior high school students. Based on some observations it is difficult to write texts because they have mastery of words and confidence in expressing ideas in written form. Using qualitative descriptive methods and tending to use student writing analysis and identify teacher difficulties in teaching writing in junior high school.The results of this study found that the teacher's ability to improve students' writing skills was more or less below average. This means that the writing skills of junior high school students are included in the poor category.In addition, the limited vocabulary mastery for students is one of the teacher's difficulties in teaching writing. Overall, this research was quite challenging to do because it not only had to understand teaching writing strategies but also because the epidemic situation made data collection difficult.